Frames That Matter: How Institutional Discourse Shapes Collective Understanding Of Crisis - Karimova Ominaxon Maxmudovna; DSc Arustamyan Y. Y. (Genius Journals, 2025)
This article examines the strategic role of framing in institutional discourse, focusing on how different actors linguistically construct meaning around high-stakes events. Grounded in the theoretical foundations of Goffman’s frame analysis and Entman’s four-function model, the study highlights how framing operates as both a cognitive shortcut and an ideological instrument. Far from being neutral, frames serve as mechanisms of power, selectively shaping public perception, moral judgment, and institutional credibility. Drawing from three distinct sources: the U.S. Environmental Protection Agency (EPA), the Smithsonian National Museum of Natural History, and BP’s official report, the analysis reveals how governmental, scientific, and corporate voices mobilize different framing devices. The EPA emphasizes state-led accountability through responsibility and oversight frames; the Smithsonian evokes ecological urgency and moral reflection through environmental devastation framing; while BP employs corporate apologia and complexity framing to deflect blame and depersonalize responsibility. Through comparative framing analysis, the article demonstrates how these discourses not only reflect distinct communicative aims but also engage in symbolic contestation over narrative ownership. Ultimately, the study affirms that framing is not merely about structuring information, but about establishing authority, shaping collective memory, and influencing how crises are publicly understood, morally evaluated, and historically remembered
Keywords: framing theory; institutional discourse; media framing